Comparison of kinematics and electromyography in the last repetition during different maximum repetition sets in the barbell back squat - Falch, Hallvard Nygaard; Hegdahl Gundersen, Andreas; Larsen, Stian; Estifanos Haugen, Markus; van den Tillaar, Roland (PeerJ, 2024)
Background The barbell squat is an exercise used to strengthen the lower limbs, with implications for both performance in sports and improving movement during everyday tasks. Although the exercise is being trained across a variety of repetition ranges, the technical requirements may vary, affecting appropriate repetition range for specific training goals. Methods A randomised within-subject design was used to compare kinematics and surface electromyography (EMG) in the lower extremities during different concentric phases (pre-, sticking- and post-sticking region) of the last repetition when performing squats at different repetition maximums (RMs). Thirteen strength-trained men (age: 23.6 ± 1.9 years; height: 181.1 ± 6.5 cm; body mass: 82.2 kg, 1RM: 122.8 ± 16.2, relative strength: 1.5 ± 0.2 x body mass in external load) performed a 1, 3, 6, and 10RM squat, in a randomised order. Results The main findings were that barbell-, ankle-, knee- and hip kinematics were similar across different repetition ranges, except for a smaller trunk lean at 1RM in the pre-sticking region compared to other repetitions and in the sticking region compared to 10RM (p ≤ 0.04). Furthermore, 1RM revealed significantly higher EMG amplitude in the vastus lateralis, gastrocnemius and soleus in the sticking and post-sticking regions when compared to 10RM. It was concluded that 10RM may locally fatigue the vastus lateralis and plantar flexors, explaining the lower EMG amplitude. The observed differences indicate that requirements vary for completing the final repetition of the 10RM compared to the 1RM, an important aspect to consider in training to enhance 1RM strength.
Keywords: Strength; Load; Angles; Muscle activity; Specificity